The Man in the brown suit - Christie, Agatha, 1890-1976.; Bairi; Hughot (London : Harper, 2007)
Anne Beddingfield is a young woman looking for adventure, but adventure finds her when a strange man is killed right in front of her. Scotland Yard's verdict is accidental death, but Anne does not agree. Determined to track down a mysterious bystander, she embarks on a hight-risk expedition that takes her across Africa and into dangers.
Cartoon book edition.
Keywords: Comics and cartoons; Mystery ficton; Private investigators -- England -- Fiction